The effect of referral templates on out-patient quality of care in a hospital setting: a cluster randomized controlled trial - Wåhlberg, Henrik; Valle, Per Christian; Malm, Siri; Hovde, Øistein; Broderstad, Ann Ragnhild (BMC Health Services Research, 2017)
Background - The assessment of quality of care is an integral part of modern medicine. The referral represents the handing over of care from the general practitioner to the specialist. This study aimed to assess whether an improved referral could lead to improved quality of care. Methods - A cluster randomized trial with the general practitioner surgery as the clustering unit was performed. Fourteen surgeries in the area surrounding the University Hospital of North Norway Harstad were randomized stratified by town versus countryside location. The intervention consisted of implementing referral templates for new referrals in four clinical areas: dyspepsia; suspected colorectal cancer; chest pain; and confirmed or suspected chronic obstructive pulmonary disease. The control group followed standard referral practice. Quality of treatment pathway as assessed by newly developed quality indicators was used as main outcome. Secondary outcomes included subjective quality assessment, positive predictive value of referral and adequacy of prioritization. Assessment of outcomes was done at the individual level. The patients, hospital doctors and outcome assessors were blinded to the intervention status. Results - A total of 500 patients were included, with 281 in the intervention and 219 in the control arm. From the multilevel regression model the effect of the intervention on the quality indicator score was insignificant at 1.80% (95% CI, −1.46 to 5.06, p = 0.280). No significant differences between the intervention and the control groups were seen in the secondary outcomes. Active use of the referral intervention was low, estimated at approximately 50%. There was also wide variation in outcome scoring between the different assessors. Conclusions - In this study no measurable effect on quality of care or prioritization was revealed after implementation of referral templates at the general practitioner/hospital interface. The results were hindered by a limited uptake of the intervention at GP surgeries and inconsistencies ...